Features of project activity in professional education - Yury Pavlovich Vetrov (Вестник Майкопского государственного технологического университета)
The novelty of the research consists in the need to introduce project activities of students into the educational process in accordance with the requirements of standards. The article deals with the problem of organization and implementation of project activities of students in the educational process of a university (college). The purpose of the article is to identify characteristic features of project activities in the educational process, to determine conditions for the effectiveness of project activities and possible implementation difficulties. The research methods used are theoretical analysis, synthesis, generalization. The following provisions reflect the results of the research: The qualities of a modern graduate demanded by employers and formed in the process of its inclusion in project activities have been revealed. The author concludes that the project activity is a didactic means of vocational training. Goals and objectives of project activities in teaching students have been defined. The author gives a generalized description of the role and activities of a teacher and a student included in the project activity. The main types of project activities have been identified depending on various grounds: a substantive area, the nature of contacts in the project, a number of project participants, duration of the project, a dominant activity of a student in the project. Main difficulties and mistakes in the implementation of students' project activities in the educational process of vocational education institutions have been presented on the basis of the analysis of theoretical data. The author defines the conditions under which the organization of students' project activities in the educational process of vocational education organizations will be the most optimal. The conclusions: the organization of project activities of students in the educational process will be more successful with the implementation of conditions and consideration of errors and difficulties of the implementation of project activities from both teachers and students.